An unusual frequency dispersion of the dielectric permittivity maxima at temperatures around the tetragonal-cubic phase transition of methylammonium lead iodide - Minussi, F. B. [UNESP]; Reis, S. P. [UNESP]; Araujo, E. B. [UNESP] (Amer Inst Physics, 2020)
We report studies on the unusual frequency dispersion of the dielectric permittivity maxima of methylammonium lead iodide pellets at temperatures around the tetragonal-cubic phase transition. The origin of this observed permittivity response was studied in terms of grains and grain boundaries' contributions in impedance, electric modulus, dielectric permittivity, and electrical conductivity. From theoretical fits of impedance and electric modulus measurements at different temperatures over a frequency range of 10(3)-10Hz, the reconstructed contributions of the grain boundary and grain permittivities show peaks around 339K and 384K, respectively. The origin of the grain boundary permittivity peak is discussed in terms of heterogenic ionic conduction associated with I- and MA(+) ions in MAPbI(3), while the peak in grain permittivity at high temperature is in terms of ionization of intrinsic carriers. The high value of the grain dielectric permittivity ( epsilon g = 1193 ), compared to the reconstructed grain boundary permittivity ( epsilon g b = 53 ), suggests a possible relaxor ferroelectric behavior with a diffuse phase transition for methylammonium lead iodide. The difficulties in confirming the ferroelectric nature of this halide perovskite based on impedance and electrical module data are also discussed.